Penggunaan Celebrity Endorsement Dalam Periklanan Online (BTS Sebagai Celebrity Endorser Perusahaan Fila) - Luthfina, Syanaz (Jurnal InterAct, 2020)
In this digital era marked by massive use of internet and social media in society, there is the importance of social media as a popular channel for companies to advertise their products. The rise of internet and social media shows the significance and promising business opportunities for online advertisement implementation. One way to advertise is through celebrity endorsers. Fila, a worldwide sportswear company, appointed BTS, the popular K-pop boyband, as their representative endorser. This research uses the theory of celebrity endorsement,social media, and online advertisement. The research design uses qualitative approach. For data collection this study relies on literature review and online observation. This study examineswhy BTS is a credible celebrity endorser, as well as the advantages and risks of having celebrity endorsers in social media and how it implemented in official social media accounts of Fila. Results shows that BTS appointed as an endorser because of their good image that represents Fila products, and BTS’ image as a boyband group that has enthusiasm, positivity, and written communication with fans it’s in harmony with Fila’svalue. Results also shows BTS is a credible endorser and able to personalize Fila products. BTS has the expertise, trust, as well as likability from their fans all over the world.